(untitled) (ASEAN Engineering Journal, 2022)
In recent years, discharging flood water downstream of the dams by the use of ski-jump bucket has become increasingly common. However, due to impact of trajectory unexpected scour holes have occurred in the tail channel, leading to expensive remedial work. One of the threats is that scouring caused by the impact of trajectory, which not only affects the safety of the river bed or tail channel but it also affect the safety of the dam, spillway and bucket. To minimize this risk of scouring, a model studies using deflector along both sides of the ski-jump bucket is performed. The model is designed in the scale of 1:50. The experiments are performed in a flume of 20 m long, 0.7 m wide and 1.2 m deep. The work is carried out using prototype data of the Ukai dam Spillway. The experimental observations are taken with and without presence of deflector. In the current study, a convergent deflector arrangement on a bucket forces a water jet to impact in mid-air, allowing it to fall down with a downscale impact. The results show that using a deflector can minimize scour by 16.51% to 28.28%.